Managerial Decision-Making and Risk Management in Indonesian Higher Education Institutions: A Literature Review - Riris Kustiningtias; Eva Hadiana; Melisa Rohmatun Nisa’ A; Ana Zakiyah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Higher education institutions operate in complex and uncertain environments shaped by digital transformation, financial pressures, governance challenges, and increasing stakeholder demands. These conditions expose institutions to strategic, operational, academic, and reputational risks that influence managerial decision-making and institutional sustainability. Objectives: This study aimed to conduct a literature review and synthesize the literature on risk management practices and their implications for managerial decision-making in higher education institutions, with particular attention to governance and performance outcomes. Methods: A literature review was conducted using Scopus, Web of Science, and Google Scholar. Articles published between 2020 and 2025 were screened using predefined inclusion and exclusion criteria. Titles and abstracts were reviewed, followed by full-text assessment. Data were extracted on study design, thematic focus, and managerial implications. A thematic synthesis approach was applied to identify recurring patterns across studies. Results: The findings indicated that risk management improved the effectiveness of quality assurance, institutional governance, service quality, and organizational performance. Institutions with higher risk management maturity demonstrated stronger integration of governance structures, strategic planning, and performance monitoring systems. Risk-based approaches enhanced evidence-based managerial decision-making, institutional accountability, and academic competitiveness. However, fragmented implementation and limited governance capacity remained significant challenges. Conclusions: Risk management functions as a strategic governance instrument that strengthens managerial decision-making and institutional resilience in higher education. Integrating risk-based frameworks into governance and performance systems is essential for sustainable institutional development, particularly in complex and rapidly changing educational environments.